A utilização do cálculo diferencial e integral para o cálculo de volume de sólidos geométricos - Lima, Jandean da Silva (2016)
This paper discusses the concept of volume and use of the integration process as a method for the volume calculation of geometric solids studied in high school, aiming to provide the mathematics teacher of basic education an alternative tool for the justification of the solids volume of formulas geometric, different from what is used in almost all the textbooks of basic education, as well as in most geometry books, which is the principle of Cavalieri. Understanding that the textbook is the main reference of most mathematics teachers of basic education, and knowing that the principle of Cavalieri is the central tool in the statements of volume formulas in geometry books and textbooks of Mathematics, we conclude that the teacher it does not have research material to bring new approaches to the justification of the formulas in question. This fact motivated the construction of this work, whose goal is to provide the mathematics teacher of primary school text that serve as a source of research on the use of differential and integral calculus to calculate the volume of geometric solids, bringing the statements of formulas most geometric solids studied in high school via integrations. With the study of this text, we expect the teacher to deepen their knowledge related to spatial geometry, in particular the concept of volume and involved statements. The methodology used for the construction of this work was the literature, so that this research was made from analyzes and reviews of books related to the topic. The result of this work is summarized in the creation of a text containing a precise and systematic study on the concept of volume as well as a different approach about the statements of geometric solids volume formulas, using as a tool the integration process. We conclude that integration is an excellent tool for calculating volumes, solving of simple problems that would become very complicated by the principle Cavalieri. This text may be used as a reference to search for basic education mathematics teachers who want to work with deepening classes, or preparing for the most difficult university entrance exams in Brazil.